A Silica Colloidal Mask for Randomly Surface‐textured Indium‐doped Tin Oxide for Enhancing the Power‐conversion Efficiency of Polymer Solar Cells. (14th February 2016) - Park, Jeong‐Woo; Shim, Jae Won
Abstract : Abstract : We report on the photovoltaic properties of polymer solar cells (PSCs) that utilize surface‐textured indium‐doped tin oxide (ITO) as the hole‐collecting electrode. The surface‐textured ITO was obtained by etching the ITO surface using two‐dimensional silica colloidal particles. By treating the ITO surface with polyelectrolytes, monolayer silica colloidal particles could be uniformly distributed on the ITO surface. The random patterns on the ITO surface were realized by a plasma etching process using these colloidal particles as an etching mask. Scattered reflection induced by the random patterns on the ITO surface leads to increased photon absorption in the photoactive layer. The PSC with an ITO etching depth of 30 nm exhibits an increased short‐circuit current density of 10.0 mA/cm 2 and a power‐conversion efficiency of 4.23%, compared to the reference device comprising an unpatterned ITO surface.